Estimation of Time of Concentration in the Upstream Watershed of Garroodbar Dam Using Various Methods - Mojtaba Farhadzadeh; Seyed Razi Anisheh; Parisa Maleki (مهندسی و مدیریت ساخت)
Temporal parameters are widely used in most hydrological and hydraulic models. The most commonly used temporal parameter in hydrology is the time of concentration, which is one of the most crucial hydrological variables in the design of flood control structures, dam spillways, and other hydraulic structures. Numerous methods have been proposed for estimating the time of concentration. This study aims to select the most appropriate method for estimating the time of concentration in the upstream watershed of Garroodbar Dam. The preliminary studies of this dam were conducted on the SheshRoodbar River in Savadkooh County, Mazandaran Province, to meet part of the region’s drinking water demand. For the estimation of the time of concentration in this watershed, six methods were considered: Giandotti, Bransby Williams, California, Kerpich, SCS, and Travel Time. Considering the conditions and limitations associated with each method, as well as the physical characteristics of the upstream watershed of the dam-including the main channel length, watershed area, stream slope, and the analysis of flood hydrographs recorded at the Karikola hydrometric station (located downstream of the dam)—the Travel Time method was selected as the most suitable approach. Finally, the time of concentration for the Kerikola station and the Garroodbar Dam watershed was estimated at 5.7 hours and 9.2 hours, respectively, using the Travel Time method.